Add: 1/2(x+4)+14(4x−2) . Answer should be in mixed number form

5 answers

To simplify the expression, let's start by distributing the 14 to both terms inside the parentheses:

1/2(x + 4) + 14(4x - 2)

= 1/2 * x + 1/2 * 4 + 14 * 4x - 14 * 2

= 1/2 * x + 2/2 + 56x - 28

Combining like terms, we have:

= 1/2 * x + 56x - 26

Now, let's find a common denominator to rewrite the expression:

= (1/2 * x + 56x - 26) * 2/2

= (x/2 + 112x - 52)/2

Lastly, let's simplify the expression by dividing each term by 2:

= x/4 + 56x/2 - 52/2

= x/4 + 28x - 26

Therefore, the simplified expression in mixed number form is: x/4 + 28x - 26.
are you sure
Apologies for the mistake. Let's simplify the expression correctly:

1/2(x + 4) + 14(4x - 2)

= 1/2 * x + 1/2 * 4 + 14 * 4x - 14 * 2

= 1/2 * x + 2/2 + 56x - 28

= 1/2 * x + 56x - 26

To convert the expression into mixed number form, we need to find a common denominator for the fractions. The common denominator is 2. Then, we can rewrite the expression as follows:

= (1/2 * x + 56x - 26) * 2/2

= (x/2 + 112x/2 - 26) * 2/2

= (x + 112x - 26)/2

In mixed number form, the expression is:

= (113x - 26)/2
wrong
Apologies for the mistake. Let's simplify the expression correctly:

1/2(x + 4) + 14(4x - 2)

First, let's distribute 1/2 to (x + 4):

(1/2)(x + 4) + 14(4x - 2)

= (1/2)x + (1/2)4 + 14(4x - 2)

= (1/2)x + 2 + 14(4x - 2)

= (1/2)x + 2 + 56x - 28

Next, let's combine like terms:

= (1/2)x + 56x - 26

To convert the expression into mixed number form, we need to find a common denominator for the fractions. The common denominator is 2. Then, we can rewrite the expression as follows:

= (1/2)x + (112x/2) - (26/2)

= (1/2)x + (112x - 26)/2

In mixed number form, the expression is:

= (x/2) + (112x - 26)/2

Therefore, the simplified expression in mixed number form is: (x/2) + (112x - 26)/2.